Additional VCUG-related parameters for predicting the success of endoscopic injection in children with primary vesicoureteral reflux. Issue 1 (February 2021) - Baydilli, Numan; Selvi, Ismail; Pinarbasi, Ayse Seda; Akinsal, Emre Can; Demirturk, Halis Can; Tosun, Halil; Demirci, Deniz
Summary: Introduction and objective: Prediction of vesicoureteral reflux (VUR) prognosis and decision for treatment are usually made according to the reflux grading classification. But the management of VUR is still controversial since there are difficulties in distinguishing reflux grade due to inter- and intra-observer variations. Previous studies have demonstrated that the distal ureteral diameter ratio (UDR) on voiding cystourethrography (VCUG) may be more predictive for clinical prognosis than reflux grade. We aimed to predict the success of endoscopic injection in primary VUR by creating new models that include other additional parameters (timing of reflux, delayed post-voiding contrast drainage of the upper urinary tract) as well as UDR. Study design: A total of 200 patients aged 2–15 years with primary VUR undergoing endoscopic injection were retrospectively evaluated. Demographic and clinical data for a total of 248 renal units were recorded. Besides reflux grade and laterality, distal ureteral diameter, UDR, timing of reflux [early filling, late filling or voiding] and presence of contrast delay in upper tract drainage were also assessed on VCUG. According to the complete resolution of VUR on the control VCUG at the postoperative 3rd month, the renal units were divided into two main groups: successful (n = 171, 68.9%) and unresolved (n = 77, 31.1%) Results: The failure rate of endoscopic injection was found to be 4.068 times greater with early filling reflux on VCUG, 3.076 times greater with UDR>0.24, 2.745 times greater with delayed contrast drainage of the upper urinary tract, 2.666 times greater with the presence of scar in DMSA, 2.493 times greater with bladder-bowel dysfunction and 2.341 times greater with febrile urinary tract infection. We also observed that a model in which all VCUG-related parameters were combined provided a better estimation of endoscopic injection outcomes compared to only the reflux grade (AUC: 0.903 vs. 0.604, respectively). Discussion: Distal ureteral dilatation is considered to be a more decisive factor for clinical outcomes of primary VUR rather than upper urinary tract dilatation since ureterovesical junction anatomy plays a more important role in primary VUR pathophysiology. Studies investigating new prediction models on this topic have recently become more popular. However, a consensus has not yet been achieved. Conclusion: We consider that UDR level, the timing of reflux and delayed upper tract drainage on VCUG may be more predictive parameters of endoscopic injection success compared with reflux grade, and could facilitate selecting the best candidates for surgery. SummaryTable 1 ROC curve analysis of the additional contribution of VCUG-related parameters to reflux grade for estimating endoscopic injection outcomes. SummaryTable 1   AUC, (95% CI), p value Reflux grade 0.604 (0.549–0.698), p = 0.002∗ UDR 0.704 (0.633–0.775), p < 0.001∗ Timing of reflux 0.736 (0.608–0.783), p < 0.001∗ Delayed post-voiding drainage of upper urinary tract (DPVD) 0.634 (0.528–0.681), p = 0.009∗ Reflux grade + DPVD 0.762 (0.661–0.887), p < 0.001∗ Reflux grade + UDR 0.776 (0.652–0.889), p < 0.001∗ Reflux grade + Timing of reflux 0.802 (0.796–0.952), p < 0.001∗ Reflux grade + UDR + DPVD 0.831 (0.627–0.955), p < 0.001∗ Reflux grade + DPVD + Timing of reflux 0.858 (0.803–0.961), p < 0.001∗ Reflux grade + UDR + Timing of reflux 0.883 (0.821–0.969), p < 0.001∗ UDR + Timing of reflux + DPVD 0.899 (0.824–0.973), p < 0.001∗ Reflux grade + UDR + Timing of reflux + DPVD 0.903 (0.706–0.983), p < 0.001∗ ROC: Receiver operating characteristic; AUC: Area Under Curve of Receiver Operating Characteristic; CI: Confidence interval. UDR: Distal ureteral diameter ratio; DPVD: Delayed post-voiding drainage of upper urinary tract of upper urinary tract. ∗p < 0.05 Asterisk (∗) indicates statistical significance.